2009
DOI: 10.1111/j.1651-2227.2009.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in BAER at different click rates from neonates to adults

Abstract: BAER is affected by stimulus rate more in younger children than in the older. Adult-like rate-dependent changes are reached at 1-2 years for wave I latency and I-III interval, and 3-4 years for wave III and V latencies and I-V and III-V intervals. Our BAER data at different click rates provide normal references for subjects of various ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 10 publications
3
24
0
Order By: Relevance
“…Overall, mean latencies of waves eIII and eV were within 2 SD of previously reported normative values in children using unilateral CI [Gordon et al, 2006], whereas the latencies of III and V were prolonged [Campbell et al, 1981;Beiser et al, 1985;Eggermont and Salamy, 1988;Jiang et al, 2009], especially for wave V ( fig. 2 b).…”
Section: Methodssupporting
confidence: 60%
See 2 more Smart Citations
“…Overall, mean latencies of waves eIII and eV were within 2 SD of previously reported normative values in children using unilateral CI [Gordon et al, 2006], whereas the latencies of III and V were prolonged [Campbell et al, 1981;Beiser et al, 1985;Eggermont and Salamy, 1988;Jiang et al, 2009], especially for wave V ( fig. 2 b).…”
Section: Methodssupporting
confidence: 60%
“…2 c). Again, there were no significant effects of hearing loss on electrically (R = 0.08, p = 0.73) or acoustically (R = 0.43, p = 0.05) evoked interwave latencies, al- Mean wave latencies were significantly shorter to electric than acoustic stimulation, but were comparable to normative values [Gordon et al, 2006] with electric stimulation, but not with acoustic stimulation [Campbell et al, 1981;Beiser et al, 1985;Eggermont and Salamy, 1988;Jiang et al, 1991Jiang et al, , 2009. c Interwave latencies were similar for electric and acoustic stimulation except for 7 children with severe-to-profound hearing loss in the nonimplanted ear.…”
Section: Symmetric Brainstem Function Is Preserved In Only a Portion mentioning
confidence: 93%
See 1 more Smart Citation
“…The mean of the rate for each experiment is indicated in the first column. with other studies (e.g., Yagi and Kaga, 1979;Lasky, 1984;Lina-Granade et al, 1993;Leung et al, 1998;Jiang et al, 2009;Stone et al, 2009). Table II shows the mean and standard deviation of the latencies and amplitudes of waves I, III, and V on ABR obtained using the RSA, QSD, and CONV techniques at different stimulation rates.…”
Section: Analysis Of Amplitudes and Latencies Measured With Rsamentioning
confidence: 97%
“…Following a perinatal asphyxia event, ABR abnormalities have been reported, including an elevated response threshold, an increase in wave latencies, brainstem conduction time and interpeak intervals; reduced wave amplitudes and V/I amplitude ratio (22,34,75). These electrophysiological findings have been correlated with histopathological observations, which indicated that perinatal asphyxia often causes discrete lesions in brainstem auditory nuclei (65).…”
Section: Introductionmentioning
confidence: 92%